The Contextuality of Urban Park Facilities in Indonesia: A Systematic Review of Social Aspect Identification - Ekky Nada Wijaya; Tigor Wilfritz Soadoun Panjaitan; Darmansjah Tjahja Prakasa (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2025)
In Indonesia, urban parks face serious challenges in the form of declining functionality due to limited maintenance, changing community needs and a lack of fit with the local context. Parks intended for social interaction, recreation and improving environmental quality often lose their appeal because their facilities cannot meet users' needs. Consequently, many parks have become passive spaces or have been abandoned. This study aims to systematically review the social aspects of urban park facilities in Indonesia through a systematic literature review of various empirical and theoretical studies. The analysis involves examining scientific publications, research reports, and policy documents that discuss the relationship between park facilities, user characteristics, and social behavior. The review focuses on aligning park facilities with the characteristics, behaviors, and needs of the community to support the social sustainability of public spaces. The findings show that the quality of urban parks is determined by five main social aspects: the user's sense of ownership, sense of peace, social satisfaction, local community activities and the social behavior of users. These five aspects complement each other in shaping the experience of the space. Contextual facilities are able to foster emotional bonds, create peace, increase collective satisfaction and encourage community participation. Therefore, context-based urban park planning strengthens ecological functions and ensures that public spaces remain adaptive, inclusive and meaningful to the community amidst ever-evolving urban dynamics.